The metagenomic landscape of a high‐altitude geothermal spring in Tajikistan reveals a novel Desulfurococcaceae member, Zestomicrobium tamdykulense gen. nov., sp. nov - Munavvara Dzhuraeva; Khursheda Bobodzhanova; Nils‐Kåre Birkeland (MicrobiologyOpen)
Abstract Metagenomic analysis was conducted to assess the microbial community in the high‐altitude Tamdykul geothermal spring in Tajikistan. This analysis yielded six high‐quality bins from the members of Thermaceae, Aquificaceae, and Halothiobacillaceae, with a 41.2%, 19.7%, and 18.1% share in the total metagenome, respectively. Minor components included Schleiferia thermophila (1.6%) and members of the archaeal taxa Pyrobaculum (1.2%) and Desulfurococcaceae (0.7%). Further analysis of the metagenome‐assembled genome (MAG) from the Desulfurococcaceae family (MAG002) revealed novel taxonomy with only 80.95% closest placement average nucleotide identity value to its most closely related member of the Desulfurococcaceae family, which is part of the Thermoproteota phylum comprising hyperthermophilic members widespread in geothermal environments. MAG002 consisted of 1.3 Mbp, distributed into 48 contigs with 1504 predicted coding sequences, had an average GC content of 41.3%, a completeness and contamination rate of 98.7% and 2.6%, respectively, and branched phylogenetically between the Ignisphaera and Zestosphaera lineages. Digital DNA‐DNA hybridization values compared with Ignisphaera aggregans and Zestosphaera tikiterensis were 33.7% and 19.4%, respectively, suggesting that this MAG represented a novel species and genus. Its 16S rRNA gene contained a large 421 bp intron. It encodes a complete gluconeogenesis pathway involving a bifunctional fructose‐1,6‐bisphosphate phosphatase/aldolase; however, the glycolysis pathway is incomplete. The ribulose monophosphate pathway enzymes could be used for pentose synthesis. MAG002 encodes several hydrogen‐evolving hydrogenases, with possible roles as hydrogen sinks during fermentation. We propose the name Zestomicrobium tamdykulense gen. nov. sp. nov. for this organism; it is the first thermophilic genome reported from Tajikistan.